Do short sellers anticipate late filings? - Dai, Rui; Li, Ting; Zaiats, Nataliya; Zhao, Xinlei (Journal of Corporate Finance, 2021)
Exploiting the setting of firms that are unable to disclose timely financial reports and thus must file with the U.S. Securities and Exchange Commission (SEC) the NT 10-K (Q) report, this study examines whether short sellers target firms with financial reporting weaknesses. We find that short interest increases in firms prior to the NT 10-K (Q) filing, suggesting that short sellers identify and target firms that cannot file their financial reports in a timely manner. Short selling is positively significantly related to subsequent late filing status, and is more pronounced in late filers with high newswire activity and with accelerated filing deadlines. Short selling of late filing firms is significantly negatively related to subsequent performance thereby suggesting that short sellers' trades pertinent to late filers are profitable. Overall, the results underscore a high information processing ability of short sellers in the setting of firms that exhibit financial reporting deficiencies.